Tingkat Keberdayaan Masyarakat dalam Program Pemberdayaan Masyarakat di Kota Banjarmasin dan Kabupaten Tanah Laut - Hairi Firmansyah (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The purpose of this study is to analyze the achievement of empowerment indicators (degree and empowerment bases) of community empowerment programs. This study was a survey research with quantitative research approaches. The respondents, consist of 60 people, were taken with multistage sample random sampling techniques (simple random stratified). The samples were subjected to community members or beneficiaries of community empowerment programs undertaken in the Banjarmasin City and Tanah Laut District. The results showed that the level of community empowerment at the Urban Poverty Program (P2KP), which was conducted in Banjarmasin City, could not afford the empower its targeted communities or beneficiaries, so the program could not deserve to be called as the community empowerment program. Similarly, the National Program for Community SelfEmpowerment – Sub-districts Program Development (PNPM-PPK) that held in the Tanah Laut District was also unable to empower its targeted communities or beneficiaries, so it could not deserve to be called as a community empowerment program. Group dynamics and the role of facilitators were the factors that affect the empowerment.